Living with diabetes: literature review and secondary analysis of qualitative data. Issue 3 (14th February 2020) - Stuckey, H.; Peyrot, M.
Abstract: Aim: To review the published qualitative literature on the lived experience of people with diabetes, describe the emerging findings and research methods over the last 25 years, and make recommendations for future research. Methods: We describe a 'Next‐Generation' mixed‐method approach to reporting qualitative data that combines the advantages of traditional qualitative analysis (assessing depth of meaning from participants themselves) with those of descriptive analysis (assessing breadth and representativeness). We used our Next‐Generation approach to conduct a secondary analysis of qualitative data derived from a systematic search of PubMed. A formal coding scheme was developed and systematically applied to 2050 respondent quotations contained in the 74 selected articles; inter‐rater agreement was high (κ = 0.90). Quotations were aggregated at the level of the article and reported to assess both narratives and numerical counts of the data. Results: The rate of qualitative research on the lived experience of diabetes has increased over the last 25 years. Both positive and negative aspects of lived experience were reported, although the former was less common. Data from many different populations were reported, but most studies emphasized breadth of coverage over depth. Some findings are well established and there is little benefit to repeating these studies. Best practices of qualitative methodology were often not utilized. Conclusions: The amount of qualitative research in diabetes is substantial and increasing. We recommend that future research be focused on specific understudied topics rather than repeating existing research. We also provide recommendations for how qualitative study methodology can be improved by implementing the Next‐Generation approach. What's new?: The lived experience of diabetes is important in healthcare research and practice, and qualitative research is well suited to describing personal experience. No systematic review has reported the findings of the qualitative diabetes psychosocial research literature using both narrative and numerical data. We develop and utilize a mixed‐method approach for synthesizing qualitative data from multiple studies. We found that negative experiences receive more attention than positive experiences. There is a need for high‐rigour analysis of in‐depth qualitative studies focused on particular aspects of the lived experience of diabetes.